A Tale of Two Adaptors: the Role of Two Adaptor Proteins in Pseudomonas Aeruginosa CHP Chemosensory System Signal Transduction and Implications for Chemosensory Array Formation - (:unkn) unknown (My University, 2020)
Bacteria use chemosensory systems to coordinate environmental signals to direct chemotaxis and make lifestyle decisions such as surface attachment and biofilm formation. Chemosensory systems form extended arrays with pseudo-hexagonal symmetry that are essential for efficient signal transduction. These arrays consist of three essential components: Methyl-Accepting Chemotaxis proteins (MCPs), which receive signals, a histidine kinase to coordinate cell responses through phosphorylation of response regulators, and an adaptor protein to transduce conformational change and facilitate array formation. Pseudomonas aeruginosa uses four chemosensory systems to control flagellar-based motility, type IV pili-mediated twitching motility and acute virulence, and biofilm formation. The Chp chemosensory system regulates two outputs: direct actuation of type IV pili supports twitching motility, and modulation of intracellular levels of cyclic-AMP (cAMP) regulates pilus biogenesis and acute virulence. In the Chp chemosensory arrays conformational changes are transduced from a single MCP, PilJ, to the histidine kinase, ChpA, via two adaptor proteins, PilI and ChpC. Using molecular techniques, we determined functional roles for PilI and ChpC. Our results show that PilI is essential for signal transduction and can facilitate twitching motility without ChpC in the presence of excess cAMP. ChpC serves as a cooperative adaptor for signal amplification necessary for efficient modulation of intracellular cAMP levels. We also investigated the interactomes of each adaptor and found that PilI and ChpC interact with each other, but curiously, neither PilI nor ChpC can self-interact. Additionally, our findings suggest PilI is the only adaptor protein that can interact with the histidine kinase ChpA. Based on the interactomes and functional roles of PilI and ChpC, and the known universal architecture of chemosensory arrays, we constructed a model for Chp chemosensory array formation. This study develops a method to understand and predict chemosensory array formation in lieu of directly visualized structural data and could be used to better understand how other chemosensory systems that incorporate multiple adaptor proteins function. This study also offers insight into Chp system function and suggests multiple potential avenues for further study.
Keywords: Chemosensory Arrays; Chemotaxis; Pseudomonas; Twitching Motility